Analysis of content of selected critical elements in fly ash - Makowska, Dorota; Wierońska, Faustyna (GeoScience Engineering, 2016)
Due to European Union new mineral policy, it is required to search for new sources of raw materials. Coal fly ash have long been considered as a potential source of a number of critical elements. The paper presents the results of examinations of the contents of selected elements, i.e. beryllium, cobalt, chromium and germanium in fly ash from Polish power plants. The results of the conducted investigations indicate that the examined ash samples from bituminous coal combustion cannot be treated as a potential source of the analyzed critical elements. The content of these elements in ash, though slightly higher than their average content in the sedimentary rocks, is, however, not high enough to make their recovery technologically and economically justified.